2009
DOI: 10.1161/circulationaha.108.834176
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Level of Life Enjoyment and Risks of Cardiovascular Disease Incidence and Mortality

Abstract: A lower perceived level of life enjoyment was found to be associated with higher risks of cardiovascular disease incidence and mortality among middle-aged men, suggesting a protective role of positive psychological conditions on cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
61
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 42 publications
(43 reference statements)
7
61
0
1
Order By: Relevance
“…The prospective association between positive affect and CHD was not reliant on self-report measures of affect and remained robust after adjusting for age, sex and cardiovascular risk factors, including depression and hostility. These associations are corroborated by other longitudinal prospective studies that have controlled for important covariates and biological risk factors (Shirai et al, 2009;Tindle et al, 2009).…”
Section: Introductionsupporting
confidence: 75%
“…The prospective association between positive affect and CHD was not reliant on self-report measures of affect and remained robust after adjusting for age, sex and cardiovascular risk factors, including depression and hostility. These associations are corroborated by other longitudinal prospective studies that have controlled for important covariates and biological risk factors (Shirai et al, 2009;Tindle et al, 2009).…”
Section: Introductionsupporting
confidence: 75%
“…Similarly, in a study of nearly 8,000 British civil servants, greater life satisfaction was associated with a reduced risk of CHD after accounting for relevant risk factors (Boehm, Peterson, Kivimaki, & Kubzansky, 2011a). Another study of approximately 88,000 Japanese men and women replicated these results over a median of 12 years (Shirai et al, 2009). In men, low life enjoyment was associated with an increased risk of nonfatal CVD (HR ϭ 1.23, 95% CI [1.05, 1.44]), and mortality from CVD (HR ϭ 1.61, 95% CI [1.32, 1.96]).…”
Section: Ppwb and Cardiovascular Health Disease-related Endpointsmentioning
confidence: 77%
“…Self-rated health has an established association with mortality (26), and is an integrated indicator of subjective physical and mental symptoms and health appraisals (27). However, in this sample, these factors accounted for only approximately 30% of the protective effect of PA. Other recent studies of mortality that used retrospective measures of wellbeing have demonstrated greater attenuation of effects when sociodemographic factors, health, and health behavior are taken into account (6,9,28).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that positive affective states and other measures of well-being are associated prospectively with longer survival and reduced risk of diseases of older age (3)(4)(5)(6)(7)(8)(9). Effects are maintained after initial health status and established risk factors are taken into account, and may also be independent of negative states such as depression (3,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation